2014
DOI: 10.14202/vetworld.2014.172-176
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of various cultural enrichment methods for the detection of selected food borne bacterial pathogens

Abstract: Aim:The study was conducted to evaluate the performance of different enrichment broths such as Tryptic Soy Yeast extract Broth (TSBYE), Brain Heart Infusion broth (BHI), Nutrient Broth (NB), Luria Broth (LB) and Peptone water (PW) for the detection of Listeria monocytogenes, Yersinia enterocolitica, Staphylococcus aureus and Salmonella enterica Typhimurium. Materials and Methods:The bacterial strains were procured from Institute of Microbial Technology (IMTECH), 0 0Chandigarh. Growth of these food borne pathog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…It could be concluded that the lab-made e-nose is able to detect rapidly the presence of bacteria L. monocytogenes and B. cereus on TSB media. For the future, it could be used to identify the presence of L. monocytogenes or B. cereus contamination in the routine and fast assessment of food products in animal quarantine.Listeria monocytogenes causes the highest case of hospitalization (up to 91%) among other foodborne illnesses [4]. Listeriosis is infectious to humans and mammals, including the ruminant and monogastric animals.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…It could be concluded that the lab-made e-nose is able to detect rapidly the presence of bacteria L. monocytogenes and B. cereus on TSB media. For the future, it could be used to identify the presence of L. monocytogenes or B. cereus contamination in the routine and fast assessment of food products in animal quarantine.Listeria monocytogenes causes the highest case of hospitalization (up to 91%) among other foodborne illnesses [4]. Listeriosis is infectious to humans and mammals, including the ruminant and monogastric animals.…”
mentioning
confidence: 99%
“…Listeria monocytogenes causes the highest case of hospitalization (up to 91%) among other foodborne illnesses [4]. Listeriosis is infectious to humans and mammals, including the ruminant and monogastric animals.…”
mentioning
confidence: 99%